(untitled) (PANGEEA, 2025)
ABSTRACT: This study present some key data from the life and work of Alexandru Ioan Cuza (1820-1873) - the first ruler and founder of the modern Romania state. We can find here biographical guidelines, his physical qualities as well as his merits as ruler, which attracted a well-deserved, extraordinary and everlasting sympathy of his people but also the implacable animosity of his adversaries. Affected by the profound and vast reforms of the ruler, and also by his exceptional personality of humane vibration, his political enemies gathered around former revolutionary freemasons C.A. Rosetti and Ion C. Bratianu and organised the conspiracy of February 11th, 1866 which forced the ruler to abdicate and take exile for 7 years, until his death. The itinerary through the country and abroad ends with underlining the actions of this great ruler in favour of the ordinary people and the progress of the country, to the dimensions that none of his descendents as heads of state could ever reach. Keywords: middle of the nineteenth century; the first ruler of the modern Romania; extraordinary sympathy; profound reforms; conspiracy; abdication; exile.